The Changing Phases of Physical Education and Sport in Africa: Can a Uniquely African Model Emerge?1 - Amusa, Lateef O. (ACTIVIDAD FÍSICA Y CIENCIAS / PHYSICAL ACTIVITY AND SCIENCE, 2022)
When I was approached to give a keynote address at this auspicious occasion of the 17th biennial conference of the International Society for Comparative Physical Education and Sport (ISCPES), a lot of topics came to my mind because there are lots of issues surrounding physical education and sport in Africa. After many considerations I decided to speak on the title “The Changing Phases of Physical Education and Sport in Africa: Can a Uniquely African Model Emerge?” This presentation will therefore follow the format below: 1. Introduction 2. The adoption of “westernized” models of Physical Education (PE) and Sport 3. Post Independent African Physical Education and Sport 4. What do all these mean? 5. The way forward (African renaissance) 6. Conclusion